Hubungan Kecerdasan Spiritual Dengan Minat Pada Proses Belajar Siswa Kelas XI - siti maftuhah; Wahidah Fitriani (JCOSE Jurnal Bimbingan dan Konseling, 2023)
Student saturation in the learning process that is often experienced by middle and upper students is a problem that is often encountered. Because in the learning process there is a process of changing circumstances with the use of the environment and social interaction which in the process takes not a little time so as to affect the interest in each student, with the concept formulated by several experts defining that the success of the learning process is influenced by many factors. One of them is internal factors such as spiritual intelligence and interests possessed by each student. Spiritual intelligence is a counterweight in functioning multiples of intelligence in each individual and interests that support success in the learning process. Because success in it is a form of student effort, the purpose of the study is to clarify the relationship between spiritual intelligence and students' interest in learning.Quantitative correlational is the method used in this study, as well as observation as another source of data. The population of this study was 143 students of class XI Madrasah Aliyah Darnnaim, with a sample of 30 respondents through the use of random sampling techniques. Generates a positive relationship between spiritual intelligence and interest in the learning process (0.651) with a strength of relationship of (65%) with significant value acquisition between the two. hence it is evident that there is an attachment between spiritual intelligence and interest in the learning process of class XI students of Madrasah Aliyah Darunna'im. Key word : Spiritual intelligence,Interest, Learning Process.